Management of residual mucogingival defect resulting from the excision of recurrent peripheral ossifying fibroma by periodontal plastic surgical procedure - Sanjeev Kumar Salaria; Neha Gupta; Vineet Bhatia; Amit Nayar (Wolters Kluwer Medknow Publications, 2015)
Peripheral ossifying fibroma (POF) is a local gingival reactive lesion, thought to be originating from the superficial periodontal ligament. It is found most often in the anterior maxilla with predilection for females and high recurrence rate. Clinically, the lesion is observed in gingiva or interdental papilla and manifested either as sessile or pedunculated mass which may appear ulcerated or erythematous or exhibit no color difference from the adjacent healthy gingival tissue. The present case report describes the diagnosis, treatment of POF, and immediate management of residual functional and cosmetic mucogingival defect which originated as a sequel of excisional biopsy of recurrent POF by utilizing modification of Grupe and Warren technique (modified laterally displaced flap). Clinical healing was uneventful at 2 weeks, and excellent coverage of residual mucogingival defect without any evidence of recession and or recurrence of POF was observed at surgical site 9 months postoperatively.